Axial Equilibrium Distance and Positioning of Particles in a Laminar Tube Flow. Issue 12 (5th November 2013) - Matulka, P.; Fischer, M.; Ehrhard, P.; Walzel, P.
Abstract Particle transport in a laminar tube flow at low Reynolds numbers leads to accumulation of particles at specific equilibrium radii. The equilibrium radius depends on the particle size. Small particles find their equilibrium radius near the wall and large particles near the tube axis. During their radial migration to the equilibrium position, the particles move in axial direction with the flow. In an experimental setup, the axial equilibrium distance is measurement for several tube Reynolds numbers. The axial equilibrium distance is the distance a particle migrates in the flow direction, until it reaches its radial equilibrium position. The results are compared with CFD‐simulations of single particle movement in a laminar tube flow.